Role of IoTs and Analytics in Efficient Sustainable Manufacturing of Consumer Electronics - Jahan, Sakila Akter; Sazu, Mesbaul Haque (International Journal of Computing Sciences Research, 2023)
Purpose – analytics has ushered in a new wave of changes in the manufacturer world. It presents manufacturing firms with efficient product manufacturing, personalization, and improvement in the way product is manufactured. However, debates arise in the implementation of these methods in some segments of the manufacturer, like electronic products, which are normally based on large-scale product manufacturing and prolonged supply chains (SC). Method – Using examples set by pieces of literature to recognize different ways that enable TSM, the paper derives different useful techniques The study develops a conceptual framework to explore if analytics coupled with different product manufacturing consumer electronics (CE) can provide for a top-class sustainable (TSM) product manufacturing system. Through a purposive sampling of 419 consumer electronics manufacturer companies applying secondary and primary data, the study explored dynamic product manufacturing processes, the role of analytics, and its impact on TSM product manufacturing. Results – The study discovers several uses of DM principles to evaluate the current product manufacturing processes worked for larger customer product CE by using analytics and industry analysis. Conclusion – The evaluation’s suggested framework mentioned in this research has a deeper impact on planning, and comprehension relationships, among factors of data analytics and TSM product manufacturing.   Recommendations – Usage of the Internet of Things (IoT) and analytics in a manufacturing system can significantly improve the efficiency and sustainability of manufacturing CE. Thus, manufacturers can greatly benefit by implementing these tools and should explore ways to do so. Research Implications – The novel study has several implications, demonstrating how sustainable efficient manufacturing could be achieved using tools like IOTs and analytics.